Global progress on adaptation implementation - Leiter, Timo; Ajibade, Idowu; Njuguna, Lucy (UNEP, 2023)
The UNEP Adaptation Gap Report (AGR) series provides an annual science-based assessment of the global progress on adaptation planning, financing, and implementation. It also explores options for enhancing and advancing national and global adaptation efforts and provides an in-depth analysis of selected issues of interest. In addition to the update on adaptation planning and implementation, the 2023 edition provides a more in-depth finance assessment chapter and includes a thematic deep-dive chapter on loss and damage. The report also highlights key case studies.